MyD88 TIR domain higher-order assembly interactions revealed by microcrystal electron diffraction and serial femtosecond crystallography - Max T. B. Clabbers (Nature Portfolio, 2021)
MAL and MyD88 are downstream adaptors of Toll-like receptors (TLR) and the MAL TIR domain forms filaments in vitro, which in turn nucleate the assembly of crystalline arrays of the MyD88 TIR domain. Here, the authors present the structure of these MyD88 TIR crystalline arrays solved by both microcrystal electron diffraction and serial femtosecond crystallography, and they show with mutagenesis experiments that MyD88 interface residues are important for TLR4 signaling in vivo.